1998
DOI: 10.1038/bjc.1998.119
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of matrix metalloproteinases in activated c-rasHa-transfected immortalized human keratinocytes

Abstract: Summary Elevated expression of matrix metalloproteinases (MMPs), a family of secreted proteinases that degrade matrix components of basement membranes and connective tissues, is strongly correlated with malignant expression in various human epithelial cancers and epithelial cancer cell lines. We have tested whether elevated levels of MMP expression are also associated with malignant progression in human cutaneous squamous cell carcinoma. Constitutive levels of expression of steady-state mRNA and of secreted pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 36 publications
1
26
2
Order By: Relevance
“…It is interesting to note that our clone A-5 synthesizes significantly less p21, the gene product of Ha-ras, than the corresponding I-7 clone (Boukamp et al, 1990) used by Meade-Tollin et al (1998). But in spite of this lower p21 expression, A-5 shows higher expression of MMP-2, -7 and -9 than HaCaT, just like the I-7 clone.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It is interesting to note that our clone A-5 synthesizes significantly less p21, the gene product of Ha-ras, than the corresponding I-7 clone (Boukamp et al, 1990) used by Meade-Tollin et al (1998). But in spite of this lower p21 expression, A-5 shows higher expression of MMP-2, -7 and -9 than HaCaT, just like the I-7 clone.…”
Section: Discussionmentioning
confidence: 92%
“…Meade- Tollin et al (1998) reported on the expression of MMP-2, -7 and -9 in HaCaT and the cell lines A-4 of class I (see above; no corresponding clone was included in the present study), I-7 of class II (like A-5 of our study), and the class III clone II-4 (see above). By Northern blot analysis they detected expression of MMP-2 and MMP-7 mRNAs in the cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This family of proteins consists of at least 26 enzymes and can be grouped into different subtypes based on the substrate specificity and sequence characteristic (18,19). Previous studies showed that RAS oncogene up-regulated MMP-2 and MMP-9, two MMPs that played critical roles in tumor metastasis, in transformed cells (20,21). Therefore, MMPs are important mediators for RAS-induced metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…22 In addition, cell transfection with an activated H-ras increases MMP-9 gelatinolytic activity. 23,24 Since MMP activity is stimulated by uPA and plasmin, 13,14,16,17 plasmin, uPA, uPAR and MMPs could be regulated by FTIs through inhibition of Ras prenylation and activity.…”
mentioning
confidence: 99%